2023
DOI: 10.1021/acs.estlett.3c00467
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Hourly Nitrogen Oxide Emissions over East Asia from Geostationary Satellite Measurements

Tianyi Xu,
Chengxin Zhang,
Jingkai Xue
et al.

Abstract: Bottom-up emission inventories of atmospheric nitrogen oxides (NO x = NO + NO2) are usually limited to annual updates and have large uncertainties. The recent launch of the Geostationary Environmental Monitoring Spectrometer (GEMS) first provides hourly measurements of trace gas pollutants from space, enabling new insights into the diurnal variations in anthropogenic NO x emissions. In this study, we present an improved top-down estimation of NO x emission using GEMS NO2 observations and characterize the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…S6 shows the spatial distribution of average (Shen et al, 2023). For instance, Xu et al (2023) observed the minimum NO2 lifetime at noon, which can be attributed to higher photochemical reaction rates resulting from increased temperature and ultraviolet radiation 360 (Gao et al, 2023).…”
Section: Diurnal Variations Of Ground-level No2 Concentrationsmentioning
confidence: 99%
“…S6 shows the spatial distribution of average (Shen et al, 2023). For instance, Xu et al (2023) observed the minimum NO2 lifetime at noon, which can be attributed to higher photochemical reaction rates resulting from increased temperature and ultraviolet radiation 360 (Gao et al, 2023).…”
Section: Diurnal Variations Of Ground-level No2 Concentrationsmentioning
confidence: 99%
“…The divergence method has mainly been applied to TROPOMI data (primarily NO 2 , but also CO and CH 4 data, e.g., Beirle et al, 2019Beirle et al, , 2021Beirle et al, , 2023de Foy & Schauer, 2022;Dix et al, 2022;Filonchyk & Peterson, 2023;Liu et al, 2021;Lonsdale & Sun, 2023;Rey-Pommier et al, 2022Sun, 2022). Recently, the method has also been applied to other satellites such as GEMS NO 2 data (Xu et al, 2023). A study of its application to synthetic CO 2 data for the upcoming CO2M mission can be found in Hakkarainen et al (2022), which notes that a background and noise removal step must be applied to make the method robust for CO 2 data.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, one year of tropospheric NO 2 VCDs of the operational GEMS L2 v2.0 product, the scientific GEMS IUP-UB v1.0 product, the operational TROPOMI product, and 11 ground-based DOAS instruments in South Korea are compared. Evaluating the GEMS NO 2 product is important to ensure the accuracy of the product for use in emission and surface concentration estimates (e.g., Xu et al, 2023;Yang et al, 2023c). The 11 ground-based observation sites are located in different pollution regimes in South Korea which provides the opportunity to observe and analyze different diurnal variations of NO 2 .…”
mentioning
confidence: 99%